Depression and demographic characteristics related to university liders and students from Metropolitan Lima - Carranza Esteban, Renzo Felipe (2012)
In past years depression was seen as a sign, symptom or syndrome, but today is adisease like any other that attacks without distinction of age, sex, marital status,socioeconomic status. The aim of the study was to determine the level of depressionof University students in metropolitan Lima. A sample of 2005 students of bothsexes was taking between 16 and 36 years, for which we used a non-experimentaldesign a descriptive. Instruments: Beck Adapted (BDI- HA) by Carranza (2009).The results show that there is depression in Metropolitan Lima University students;23.2% have a severe level of depression, and 24.1% also moderate.